Evaluating of the Optimization of Syrian Health Organizations' Websites in Search Engines (Journal of Hama University, 2022)
The study aimed to evaluate the use of the website of Lattakia Hospitals for keywords and content in compatible with search engines from the viewpoint of the clients of this hospitals, where the descriptive analytical approach was followed describe the variables of the study and the questionnaire was used as a study tool to conducted in order to find out the difference between the average answers of the research sample members and the neutral mean of the five-point Likert scale by one-sample t test, using the statistical program SPSS 21, where the study concluded that the hospitals do not use keywords in there website in the way that is compatible with search engines, the result was different for the content, as the final evaluation for optimizations the websites, it indicated that the hospitals do not use search engine optimization techniques on the hospital websites. Therefore, the researcher recommended that the hospitals should use on there websites the many tools provided by the search engine Google to analyze keywords in order to use these words on the websites, in addition to writing content according to the rules of search engines in order to obtain an advanced ranking in the search results on the first page of the Google search engine